Life cycle assessment for bioethanol production from oil palm frond juice in an oil palm based biorefinery - Mohd Yusof, Siti Jamilah Hanim; Roslan, Ahmad Muhaimin; Ibrahim, Khairul Nadiah; Syed Abdullah, Sharifah Soplah; Zakaria @ Mamat, Mohd Rafein; Hassan, Mohd Ali; Shirai, Yoshihito (MDPI, 2019)
A study was conducted to estimate the possible environmental impacts arising from the generation of bioethanol from oil palm frond sugar juice in a theoretical oil palm based biorefinery model. A life cycle assessment (LCA) with the gate-to-gate approach was performed with the aid of SimaPro version 8.0 whereby ten impact categories were evaluated. The scope included frond collection and transportation, frond sugar juice extraction, and bioethanol fermentation and purification. Evaluation on the processes involved indicated that fermentation contributed to the environmental problems the most, with a contribution range of 52% to 97% for all the impact categories. This was due to a substantial usage of nutrient during this process, which consumes high energy for its production thus contributing a significant burden to the surrounding. Nevertheless, the present system offers a great option for biofuel generation as it utilizes sugar juice from the readily available oil palm waste. Not only solving the issue of land utilization for feedstock cultivation, the enzymatic saccharification step, which commonly necessary for lignocellulosic sugar recovery could also be eliminated.